Using family atopy scores to identify the risk of atopic dermatitis in infants - Melisa Anggraeni; Ketut Dewi Kumara Wati; Ketut Tangking (Indonesian Pediatric Society, 2014)
Background Atopic dermatitis is the first manifestation ofallergic disease in early life. Early interventions may prevent thedevelopment of allergy disease. Allergy trace cards have beenused to identify the level of allergic risk, based on family atopyscores. Because environmental factors may also influence thedevelopment of atopic dermatitis, the usefulness of the allergytrace card needs to be reevaluated.Objective To compare the incidence of atopic dermatitis ininfants aged 0-4 months with total family atopy scores of > 0 tothose with scores of 0.Methods We conducted this cohort study from June 1, 2012 toDecember 31, 2012 at Sanglah Hospital, Denpasar. Family atopyscore was tabulated from all pregnant woman in the ObstetricOutpatient Clinic and the Maternity Room. Subjects were dividedinto two groups based on their total family atopy score: those withscores > 0 and those with scores of 0. The appearance of atopicdermatitis symptoms in the infants were evaluated until theyreached 4 months of age. The incidence of atopic dermatitis intwo groups was compared using Chi-square test.Results The incidence of atopic dermatitis in this study was 10.9%.The group with total family atopy scores of 0 had a significantlyhigher incidence of atopic dermatitis than the group with scores> 0 (adjusted RR 22.5; 95%CI 8.8 to 57.0; P = 0.001).Conclusion The incidence of atopic dermatitis is higher ininfants with total family atopy score > 0 and this group has a 22.5times higher risk of atopic dermatitis compared to infants withtotal family atopy score of 0. Allergy trace cards are relevant indifferentiating the risk of atopy with regards to development ofatopic dermatitis. We suggest that family atopy scores be evaluatedduring antenatal care in order to limit the development of atopicdermatitis in infants.